Prioritizing HRM and Apprenticeships for Enhanced Productivity (New Perspective: Journal of Business and Economics, 2025)
This editorial critically examines human resource management (HRM) practices and apprenticeship readiness among industries in Nepal’s Bara-Parsa Industrial Corridor, emphasizing their pivotal role in enhancing workforce productivity and sustainability. It explores the interaction of organizational cynicism, job burnout, and perceived organizational support (POS) within Nepal’s socio-economic context, highlighting their impact on employee morale and performance. Addressing challenges such as policy gaps, gender disparity, and skill shortages, the editorial proposes actionable strategies grounded in national legal frameworks and international best practices. It calls on industry leaders and the Birgunj Chamber of Commerce and Industries (BiCCI) to formalize HR systems and institutionalize apprenticeships as strategic tools to cultivate skilled, engaged, and high-performing labor forces aligned with Nepal’s development goals.